ESTIMITATION OF OPPORTUNITIES OF SYSTEMATIZATION OF REQUIREMENTS TO EDUCATIONAL TRAINING PLANE - Семитківська, Т.; Сироїжка, І.; Кожухарь, О. (Science-based technologies, 2012)
The paper attempts to systematize the possibility of the requirements for training aircraft. The characteristics of aircraft pretending to participate in the discussion. Preliminary conclusions on the analysis of ICAO documents.